Mike Wozniak, 1998-99 Cal Poly Basketball - Patrick J. Merrill::::::photographer::: (1998)
Mike Wozniak, 1998-99 Cal Poly Basketball player, All-time Career Scoring Leader (text on verso). Wozniak on the court, Number 20.